2009
DOI: 10.1038/bmt.2009.37
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the psychosocial assessment of candidates for transplantation (PACT) scale in allogeneic BMT

Abstract: . The PACT has eight subscales, each rated on a 5-point scale, and an initial and final rating independently based on the rater's overall impressions of the candidate's acceptability for transplant. This exploratory study assessed the clinical utility of the PACT scale for psychosocial screening in allogeneic BMT. Associations of the PACT subscales and the final rating with sixteen post transplant medical outcomes were examined using the Jonchkheere-Terpstra test, the Cochran-Armitage test or the Cox proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 22 publications
0
15
0
5
Order By: Relevance
“…Previous paper showed that better scores on family support were associated with decreased risk of mortality or reduced patients' anxiety, suggesting that psycho-social care for patient family should be considered for better treatment outcome [29,35,36]. Therefore the approach in this case presentation suggests clinical availability in psycho-social care.…”
Section: Discussionmentioning
confidence: 84%
“…Previous paper showed that better scores on family support were associated with decreased risk of mortality or reduced patients' anxiety, suggesting that psycho-social care for patient family should be considered for better treatment outcome [29,35,36]. Therefore the approach in this case presentation suggests clinical availability in psycho-social care.…”
Section: Discussionmentioning
confidence: 84%
“…The decision-making process for selecting appropriate candidates for allogeneic HCT is complex and considers several patient, disease and transplant-related factors, including an assessment of social and psychological risk factors. We demonstrate that the PACT instrument can provide objective parameters to facilitate psychosocial risk assessment and builds on previous work in a smaller cohort of patients published from our center [27]. Using the PACT scale, we highlight risk factors that may identify a subgroup of vulnerable patients from a psychosocial perspective who may need additional vigilance, support and resources to successfully help them navigate the transplantation procedure.…”
Section: Discussionmentioning
confidence: 64%
“…While a possible association between survival and PACT score has been reported in solid organ transplant recipients [21], there are conflicting data on the influence of psychosocial comorbidities on HCT outcomes [22][23][24][25][26]. In a previous prospective study, we evaluated the utility of the PACT assessment and association of outcomes in HCT recipients [27]. However, this was a relatively small study with short follow-up and it did not consider sociodemographic and patient-reported factors.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] The Psychological Assessment of Candidates for Transplantation (PACT) and the Stanford Integrated Psychosocial Assessment for Transplant (SIPAT) have been used for pre-transplant psychological evaluation. [11,12] The PACT, previously used in psychosocial evaluation of transplant patients, and the modified version of PACT (mPACT) have been used for assessment in one small retrospective study of 48 LVAD patients. [13] Patients classified as low risk with higher mPACT scores had decreased 30 day readmission rates in this study.…”
Section: Discussionmentioning
confidence: 99%